Perspective Articles as Catalysts for Innovation: Addressing Critiques on Traditional Chinese Rehabilitation Exercise for Myofascial Pain [Response to Letter] - Liu X; Zhang J (Journal of Pain Research)
Xueen Liu,1 Jiale Zhang2,3 1Beijing Hepingli Hospital, Beijing, People’s Republic of China; 2Institute of Basic Theory of Traditional Chinese Medicine, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 3China Science and Technology Development Center of Chinese Medicine, Beijing, People’s Republic of ChinaCorrespondence: Jiale Zhang, Email zhang_tcm@163.com